Multidrug resistance factor - glycoprotein P in rheumatoid arthritis - I P Kolosova (Научно-практическая ревматология, 2003)
Objective. To assess expression of P-glycoprotein (Pgp) on peripheral blood (PB) lymphocytes and its changes during therapy in pts with rheumatoid arthritis (RA). Methods. 51 RA pts and 11 healthy donors (control group) were examined. 35 pts were followed up. 20 of them were treated with methotrexate (MT) and 15 with glucocorticosteroid (GCS) pulse therapy (PT). Pgp expression was examined with flow cytofluorometry with monoclonal antibodies (UIC2 PE, Immunotech). Results. Pgp expression on PB lymphocytes in RA was significantly more prominent (29,3 29,9 %) than in control group (2,5 2,0 %), P<0,01. Pgp expression did not depend on pts age and sex, duration and stage of the disease, presence or absence history of disease modifying drugs therapy. PT with GCS but not MT significantly decreased Pgp expression (from 57,2±27,0 % to 28,8135,2 %, r<0,05). Conclusion. RA patients have increased Pgp expression, which is probably biologically sensible but clinically unfavourable response of immunocompetent cells to durable application of such foreign substances as medications. PT with GCS decrease Pgp expression on lymphocytes while treatment with MT does not change it.